The new structuralism : design, engineering and architectural technologies - Oxman, Rivka; Oxman, Robert (London : Wiley, 2010)
Editorial (Helen Castle). About the Guest-Editors (Rivka Oxman and Robert Oxman). Spotlight: Visual highlights of the issue. Introduction. The New Structuralism: Design, Engineering and Architectural Technologies (Rivka Oxman and Robert Oxman). Radical Sources of Design Engineering (Werner Sobek). The renowned proponent of ultra- lightweight structures charts how his consultancy has developed a far-reaching approach to practice. Structured Becoming: Evolutionary Processes in Design Engineering (Klaus Bollinger, Manfred Grohmann and Oliver Tessmann). Structuring Strategies for Complex Geometries (Wolf Mangelsdorf). On Design Engineering (Hanif Kara). Innovative design-led engineer Hanif Kara advocates a holistic approach to architecture and engineering. Weaving Architecture: Structuring the Spanish Pavilion, Expo 2010, Shanghai (Julio Martinez Calzon and Carlos Castanon Jimenez). Optioneering: A New Basis for Engagement Between Architects and their Collaborators (Dominik Holzer and Steven Downing). Heinz Isler's Infinite Spectrum: Form-Finding in Design (John Chilton). Architectural Geometry as Design Knowledge (Helmut Pottmann). Structuring Materiality: Design Fabrication of Heterogeneous Materials (Neri Oxman). Materialising Complexity (Fabian Scheurer). Fabricating Design: A Revolution of Choice (Frank Barkow). Timberfabric: Applying Textile Principles on a Building Scale (Yves Weinand and Markus Hudert). Encoding Material (Fabio Gramazio, Matthias Kohler and Silvan Oesterle). The Return of the Future: A Second Go at Robotic Construction (Martin Bechthold). Bechthold examines the recent revival in robotic technologies in construction. A Deeper Structural Theory (Nina Rappaport). Counterpoint. Digital Solipsism and the Paradox of the Great 'Forgetting' (Neil Spiller).
boek